FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KETUBAN PECAH DINI DI RS PKU MUHAMMADIYAH GAMPING SLEMAN YOGYAKARTA TAHUN 2021-2022 - Fitnaningsih Endang Cahyawati; Thalia Pratiwi (Bajang Institute, 2024)
Premature Rupture of the Membrane (PPROM) is one of the complications that occurs when a mother gives birth. PROM is the rupture of the amniotic membranes before delivery, which occurs when the dilatation period is less than 4 cm at term or preterm gestational age. Aim of the Study: To determine the relationship among maternal age, parity, education level, and employment with cases of premature rupture of membranes in mothers giving birth at PKU Muhammadiyah Hospital, Gamping, Sleman, Yogyakarta, in 2021-2022. Research Method: This is an analytical survey with a case-control time approach. The data used in the research is secondary data originating from the results of medical record data collection for 2021-2022 at PKU Muhammadiyah Hospital, Gamping, Sleman, Yogyakarta. This research used a sample of 150 respondents' medical record data. Data analysis was carried out using the Chi-Square statistical test. This research has received an ethical statement number 134/KEP-PKU/VII/2023. Findings: There is a relationship between maternal age and cases of premature rupture of membranes; Chi-Square test results obtained a p-value of 0.011 (p < 0.05). Apart from that, there was a relationship between parity and cases of premature rupture of membranes where a p-value was obtained of 0.003 (p < 0.05). Maternal education level is also related to issues of premature rupture of membranes where a p-value of 0.000 (p<0.05) is obtained. Finally, there is a relationship between the mother's occupation and cases of premature rupture of membranes with a p-value of 0.014 (p<0, 05). From all the calculation results, researchers can conclude that there is a relationship among maternal age, parity, education level, and employment with cases of premature rupture of membranes at PKU Muhammadiyah Hospital, Gamping, Sleman, Yogyakarta. It is recommended that future researchers examine several other related factors that influence cases of premature rupture of membranes, not only take research samples from secondary data